2007
DOI: 10.1080/16823200709487165
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell: how children of same-gender parents negotiate their lives at school

Abstract: Dr Carien Lubbe is a lecturer in the Department of Educational Psychology at the University of Pretoria. Her main research interest focuses on same-gendered (lesbian/gay) families. Other research areas include the exploration of asset-based and positive psychological approaches in Educational Psychology. Carien has a sincere interest in qualitative methodologies, especially narrative research. She is currently involved in the training of psychological counsellors (Honours programme), as well as the supervision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…Some families avoided negative experiences by remaining silent about their familial identity, similar to the children in Lubbe's (2007b) study of lesbian/gay-parented families in South African schools. Children who were more open about the parents' sexual orientation often reported experiencing at least one instance of teasing or bullying.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some families avoided negative experiences by remaining silent about their familial identity, similar to the children in Lubbe's (2007b) study of lesbian/gay-parented families in South African schools. Children who were more open about the parents' sexual orientation often reported experiencing at least one instance of teasing or bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, schools are not being compelled to ensure that their teachers uphold the rights of lesbian, gay, bisexual, and 'queer' (LGBQ) individuals. (2004,(146)(147) Further educator training is imperative for South African schools, as research has shown that much of the homophobia currently in the school system originates or is perpetuated by the teachers themselves (Bhana 2012;Francis 2012;Lubbe 2007b;Msibi 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undervisningen og laererne kan til og med bekrefte fordommene som ligger til grunn for slike kommentarer. I slike mindre tolerante skolemiljø føler barn av lhbt i større grad at de må kontrollere informasjonen om foreldrene sine (Lubbe 2007).…”
Section: å Fortelle Andre Om Foreldrenes Seksuelle Orienteringunclassified